Impact of Urban Consumers’ Food Consumption Behavior Towards Food Waste - Wong, Kelly Kai Seng; Sharifuddin, Juwaidah Binti; Teng, Phuah Kit; Li, Wong Wang; Song, Lai Kok (AGRARIS: Journal of Agribusiness and Rural Development Research, 2020)
In this study, we aims to determine the factors that affect the consumers’ food consumption behaviour and further to examine the impact of consumers’ food consumption behaviour toward food waste in urban area. This study collected 400 questionnaires from the Klang Valley, Malaysia. The findings showed that there are three latent factors from the factor analysis which related to the negative food consumption behaviour, which were consumers’ negative attitude on food demand, perceived behavioural control on food waste, and subjective norm.  Multiple regression analysis showed that the negative food consumption attitude and perceived behavioural control on food waste have significant impact on the negative food consumption behaviour. Furthermore, the chi-square test showed that the percentage of food waste related to the difference level of negative consumption behaviour on food. Besides that, the Pearson Chi-square also showed that over demand for food and did not consume the food before expired date are highly significant associated with the number of food waste created by a household. In conclusion, consumers’ proper planning on food consumption, cooking, and food deliver order playing a significant role to reduce food waste in Malaysia.